Origins of commercial banking in America, 1750-1800 - Wright, Robert E. (Robert Eric), 1969- (Rowman & Littlefield, 2001)
In this book, Robert Wright argues that the ultimate causes of American economic development and transformation into a modern society can be reduced to the causes of American commercial banking. Wright analyzes why American banking arose when, and with the particular characteristics, it did.